Control of suddenly expanded flow from correctly expanded nozzles - Khan, Sher Afghan; Rathakrishnan, E. (De Gruyter, 2004)
The effectiveness of micro jets to control base pressure in suddenly expanded axi-symmetric ducts has been presented in this paper. Four micro jets of 1 mm orifice diameter located at 90° intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region were employed as active controls. The Mach numbers of the suddenly expanded flows were 1.25, 1.30, 1.48, 1.6, 1.8 and 2.0. The jets were expanded suddenly into an axi-symmetric tube with cross-sectional area 2.56, 3.24, 4.84, and 6.25 times that of nozzle exit area. The length-to-diameter ratio of the sudden expansion tube was varied from 10 to 1. The jets at all Mach numbers were correctly expanded. It is found that the micro jets can serve as active controllers for base pressure. Also, the wall pressure distribution is not adversely influenced by the micro jets.